2017
DOI: 10.1016/j.jpainsymman.2017.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Depression—A Major Contributor to Poor Quality of Life in Patients With Advanced Cancer

Abstract: Context: Quality of life (QoL) and depression are important patient-reported outcomes in cancer care. However, the relative importance of depression severity in predicting QoL remains unclear due to few methodologically sound studies. Objectives:To examine whether depression contributes to impairment of QoL irrespective of prognostic factors and symptom burden.Methods: 563 patients were included from the European Palliative Care Research Collaborative Study (EPCRC-CSA), an international, multi-centre, cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…This contrasts recent findings on depression being the main factor associated with poor QOL in patients with advanced cancer. 419 Symptoms of depression, 336 demoralization, 420 and spiritual distress 421 are common in patients with advanced cancer and longitudinal research has shown that, without intervention, these symptoms tend to worsen with greater proximity to death. 422 There is a growing evidence base for the effectiveness of psychological interventions to alleviate depression and other manifestations of distress in patients with advanced disease.…”
Section: Key Communicative Tasksmentioning
confidence: 99%
“…This contrasts recent findings on depression being the main factor associated with poor QOL in patients with advanced cancer. 419 Symptoms of depression, 336 demoralization, 420 and spiritual distress 421 are common in patients with advanced cancer and longitudinal research has shown that, without intervention, these symptoms tend to worsen with greater proximity to death. 422 There is a growing evidence base for the effectiveness of psychological interventions to alleviate depression and other manifestations of distress in patients with advanced disease.…”
Section: Key Communicative Tasksmentioning
confidence: 99%
“…13,14 When left unaddressed, these problems lead to reduced work productivity, 15,16 quality of life, 12,17 and overall survival. 18 Survivors who are coping with advanced cancer [19][20][21][22] report ongoing symptom burden and poor physical functioning that affects quality of life. 23,24 This research has led to recommendations to facilitate referrals for early access to palliative care 25 and rehabilitation care 26,27 that can improve quality of life.…”
Section: The Growth Of Cancer Survivorship Researchmentioning
confidence: 99%
“…Having identified these patients, the preeminent aim was to detail and discuss the co-occurring negative emotions (stress), impairments (quality of life, functional status, symptoms), and negative perceptions of one's life and illness that co-occurred. To do this was significant because the latter factors foster the maintenance of depressive symptoms and, conversely, depressive symptoms increase the frequency/severity of these sources of impairment and disability [31,32,[34][35][36][37][38]. Moving beyond PHQ-9 classification, the goal was provision of clinical descriptions for providers and researchers alike of the common psychological, behavioral, and symptom comorbidities experienced by such individuals, ones that, along with depressive symptoms, may impair patients' coping and functioning when they are to make choices and begin lung cancer treatment [39].…”
Section: Introductionmentioning
confidence: 99%